1998
DOI: 10.1007/s003390051124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of resonant tunneling on the imaging of atomic defects on InAs(110) surfaces by low-temperature scanning tunneling microscopy

Abstract: We have used a low-temperature scanning tunneling microscope (STM) to study the surface of heavily doped semiconductor InAs crystals. The crystals are cleaved in situ along the (110) plane. Apart from atomically flat areas, we also observe two major types of atomic-scale defects which can be identified as S dopant atoms and As vacancies, respectively. The strong bias voltage dependence of the STM image of the impurities can be explained in terms of resonant tunneling through localized states which are present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…Impurities at semiconductor surfaces are known to form resonant levels that can influence the STM tunnel current [16]. In contrast to previous attempts to explain the experiments [15], we suggest that it is not the impurity spin but the current itself generates coherent oscillations due to the tunneling of electrons with spin flip via the resonant level formed by the impurity.…”
contrasting
confidence: 90%
See 1 more Smart Citation
“…Impurities at semiconductor surfaces are known to form resonant levels that can influence the STM tunnel current [16]. In contrast to previous attempts to explain the experiments [15], we suggest that it is not the impurity spin but the current itself generates coherent oscillations due to the tunneling of electrons with spin flip via the resonant level formed by the impurity.…”
contrasting
confidence: 90%
“…[16]. The second term, representing a distinct peak, arises due to spin-flip transitions between the Zeeman-split sublevels in the dot.…”
mentioning
confidence: 99%
“…Indeed for InAs, only V As , V In , and S As dopants have been identified by these methods. 30,31 We have noted the experimental evidence for the presence of H on III-V (110) surfaces, and our DFT results also show that it should be stable, but to be visible in STM or AFM it also needs to be at most slow moving on the time scale of the scan. We can find no direct measurements of this in the literature.…”
Section: Simulated Stm For H On Iii-v (110) Surfacesmentioning
confidence: 52%
“…4,5 Similarly, on the n-type InSb͑110͒ surface it has been found that Sb vacancies are the most common type of defect. 6 On S-doped ͑n-type͒ InAs͑110͒ microscopy studies have shown that the most common defects are S atoms and As vacancies, 7,8 while a third type of defect was suggested to be In vacancies. 8 The current understanding of point defects at compound semiconductor surfaces is nicely reviewed by Ebert.…”
Section: Introductionmentioning
confidence: 99%